2022
DOI: 10.1186/s12913-022-08133-9
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding and experience of adverse event following immunization (AEFI) and its consequences among healthcare providers in Kebbi State, Nigeria: a qualitative study

Abstract: Background Vaccines used in the national immunization program are relatively safe and effective. However, no vaccine is perfectly safe. Therefore, adverse reactions may occur. This study aimed to investigate the understanding and experience of Adverse Event Following Immunization (AEFI) among healthcare workers and Routine Immunization (RI) officers. Methods Phenomenological qualitative study was conducted between June and September 2019, using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Twene and Yawson reported gaps in the knowledge of HCWs with regards to the definition of AEFI, AEFI investigation and conditions that should be reported as AEFIs in some parts of Ghana [21]. Similarly, in Nigeria, Omoleke et al reported varied and suboptimal knowledge levels of healthcare providers on AEFI definitions and classifications [22]. Also, our study showed that many frontline HCWs are not familiar with the AEFI reporting procedures-what to report, who to report to, and how to report.…”
Section: Discussionmentioning
confidence: 99%
“…Twene and Yawson reported gaps in the knowledge of HCWs with regards to the definition of AEFI, AEFI investigation and conditions that should be reported as AEFIs in some parts of Ghana [21]. Similarly, in Nigeria, Omoleke et al reported varied and suboptimal knowledge levels of healthcare providers on AEFI definitions and classifications [22]. Also, our study showed that many frontline HCWs are not familiar with the AEFI reporting procedures-what to report, who to report to, and how to report.…”
Section: Discussionmentioning
confidence: 99%
“…To date, LMICs remain challenged by access to life-saving vaccines while uptake and coverage remain sub-optimal due to health system, socio-cultural factors, and geographical disadvantages and poverty [5,8,9]. However, vaccines are not entirely safe; they may cause mild to moderate discomfort and serious adverse events that may warrant hospitalisation or lead to death [10,11]. Indeed, serious adverse events following immunisation (AEFI) caused by vaccines are rare (<1 in 1,000,000 cases).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this significant safety profile, caregivers and parents sometimes express concern and hesitancy for vaccination. The AEFI or perceived vaccine safety concern is one of the causes of vaccine hesitancy in the form of outright rejection or drop-out in many countries, including Nigeria [11][12][13].…”
Section: Introductionmentioning
confidence: 99%